Guidance and Counseling Management for Student Discipline and Responsibility in Elementary Schools - Ria Anggriani Siti Aisyah; Yosal Iriantara (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to analyze guidance and counseling management in developing discipline and responsibility among elementary school students at SDN Cibeureumhilir CBM Kota Sukabumi and SDN Mandalasari Kabupaten Sukabumi. This research employed a qualitative approach with a comparative case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving principals, guidance and counseling teachers, classroom teachers, students, and parents. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing or verification. The findings show that both schools implemented guidance and counseling management through planning, organizing, implementation, and evaluation, but with different management patterns. SDN Cibeureumhilir CBM applied a more formal, structured, and documented model through annual and semester programs, clear role distribution, rule-based services, reward and punishment, and routine evaluation. In contrast, SDN Mandalasari applied a more flexible, participatory, and contextual model through informal planning, collaborative teacher involvement, reflective activities, educational games, group projects, and direct communication with parents. The formal model was effective in strengthening students’ external discipline, compliance with rules, punctuality, and task completion. In contrast, the participatory model was effective in developing internal responsibility, student involvement, and reflective awareness. This study concludes that effective guidance and counseling management in elementary schools requires an integrated model that combines structured planning, clear organization, consistent implementation of services, reflective activities, systematic evaluation, and collaboration among principals, guidance and counseling teachers, classroom teachers, students, and parents.